Virtual First Impressions: Zoom backgrounds affect judgements of trust and competence - Now Published in PLOS ONE 10.1371/journal.pone.0291444 - Abi Cook; Meg Thompson; Paddy Ross (2023)
Trait inferences from first impressions are drawn rapidly and spontaneously. However, the Covid-19 pandemic forced interactions online introducing differential influential factors on first impressions. As such, there is an absence of research investigating video background on videoconferencing impression formation. This study explored the influence of video background, facial expression, and gender on first impressions of trustworthiness and competence. Video background affected trustworthy and competence perceptions with Plants and Book backgrounds scoring highly on both dimensions while the Home and Novelty backgrounds consistently received the lowest ratings. Happy faces were perceived as more trustworthy and more competent while female faces were also rated as more trustworthy and more competent, regardless of the background they were using. The explanations for these findings are discussed, along with future directions for research and the implications for videoconferencing use.